Changing Migratory Behaviors and Climatic Responsiveness in Birds - Bókony, Veronika; Barta, Zoltán; Végvári, Zsolt (Frontiers in Ecology and Evolution, 2019)
Change of avian migratory behavior is one of the best-studied phenomena presumably associated with contemporary climate change, yet to what degree these behavioral changes represent responses to climate warming is still controversial. We investigated the inter-specific variation in change of migratory behavior over three decades at a Central-European site, testing whether the type and extent of such changes are predicted by the species’ responsiveness to short-term variation in large-scale climatic indices. We found that species with earlier arrivals after winters with higher North-Atlantic Oscillation indices were more likely to overwinter at the study site; this behavior was more frequent in the second than in the first half of the study, although the extent of this change was not predicted quantitatively by short-term climatic responsiveness. Overwintering was more prevalent in short-distance migrants with more complex diets and larger population sizes. Furthermore, species arriving earlier after summers with higher Sahel rainfall indices increasingly advanced their first arrival date, whereas species that do not molt in the pre-breeding season increased their frequency of overwintering in more recent years. Our results demonstrate that interspecific variation in short-term climatic responsiveness predicts long-term changes in migratory behaviors, supporting that the latter are responses to climate change. Furthermore, the type of response (advancing arrivals or overwintering near the breeding grounds) depends on life history. Finally, we found that overwintering behavior during the study period predicted subsequent trends in population size, suggesting that information on temporal changes in migratory strategy may help conservation planning and risk assessment.